Insect mutualisms buffer warming effects on multiple trophic levels. Issue 1 (1st January 2014) - Marquis, Michael; Del Toro, Israel; Pelini, Shannon L.
Abstract : Insect mutualisms can have disproportionately large impacts on local arthropod and plant communities and their responses to climatic change. The objective of this study was to determine if the presence of insect mutualisms affects host plant and herbivore responses to warming. Using open‐top warming chambers at Harvard Forest, Massachusetts, USA, we manipulated temperature and presence of ants and Chaitophorus populicola aphids on Populus tremuloides host plants and monitored ant attendance and persistence of C. populicola, predator abundance, plant stress, and abundance of Myzus persicae, a pest aphid that colonized plants during the experiment. We found that, regardless of warming, C. populicola persistence was higher when tended by ants, and some ant species increased aphid persistence more than others. Warming had negligible direct but strong indirect effects on plant stress. Plant stress decreased with warming only when both ants and C. populicola aphids were present and engaged in mutualism. Plant stress was increased by warming‐induced reductions in predator abundance and increases in M. persicae aphid abundance. Altogether, these findings suggest that insect mutualisms could buffer the effects of warming on specialist herbivores and plants, but when mutualisms are not intact, the direct effects of warming on predators and generalist herbivores yield strong indirect effects of warming on plants.